Gameful self-regulation: A study on how gamified self-tracking features evoke gameful experiences - Hassan Lobna; Xi Nannan; Gurkan Bahadir; Koivisto Jonna; Hamari Juho (United States, 2022)
Gamification has become one of the top engagement technology trends of recent times. It refers to designing and transforming systems, services, and activities to afford gameful experiences as good games do, commonly implemented through the utilization of familiar features from games. However, one of the persistent problems in academia and practice has been the lack of understanding of which systems features are more or less prone to facilitate which dimensions of the gameful experience. We investigate the relationships between user interaction with features related to goal-setting, self-tracking as well as prompts, and gameful experiences (accomplishment, challenge, competition, guidance, immersion, playfulness, and sociability) through a survey (N=201) in a gamified exercise service. Goal-setting and prompt features were positively associated with most dimensions of the gameful experience whereas self-tracking features were negatively associated with immersion and sociability while positively associated with feelings of accomplishment.
Proceedings of the 53rd Annual Hawaii International Conference on System Sciences